Impacts of Situational Factors on Consumers' Adoption of Mobile Payment Services: A Decision-Biases Perspective. Issue 11 (2nd July 2020) - Chen, Xiaogang; Su, Libo; Carpenter, Darrell
ABSTRACT: The academic community has accumulated rich knowledge on key mobile payment service (MPS) characteristics that significantly influence consumer adoption. However, a principal assumption underlying the extant literature is that consumers work within a rational decision-making paradigm when making MPS adoption decisions. There is little MPS adoption research that empirically tests consumer adoption behavior from the alternative decision-biases perspective. Our findings demonstrate that MPS adoption behavior is a result of interactions between MPS characteristics and situational factors (i.e., purchase intention and time pressure). Further, our findings suggest that consumers' decisions on MPS adoption do not necessarily adhere to rational behavior expectations and there are boundaries to conditions where rational MPS adoption decisions apply. Lastly, our findings reveal that situational factors interactively influence MPS adoption decisions.